Biology data book - Altman, Philip L.; Katz, Dorothy Dittmer (Biological handbooks., 1972)
This book has been compiled to present numerical data of biology and medicine in a convenient and accessible form for reference, and to standardize accepted constants as a basis for correlation, establish common standards for statistical studies, and provide normal values for research.